MONITORING OF WATER TREATMENT PLANT EMPLOYING INTERNET OF THINGS - Andrianto, Dian Andri; Marwanto, Arief Marwanto; Suryani, Suryani Alifah (Journal of Telematics and Informatics, 2017)
In water treatment process, highly temperature and humidity can lead to rapid evaporation, thus increasing uses of coagulants. It influence degree of acidity or pH. Therefore, it is necessary to monitor its conditions gradually. This work proposes a real-time monitoring of temperature, humidity and pH in the water treatment plant using internet of things. The system prototype was implemented using DHT22 and pH sensors to measure the physical conditions, Arduino UNO to process the data, ESP8266 to send the data into Internet Cloud Server over MQTT protocol. The prototype was measured in the plant comparing with the conventional instruments. The results show that error of temperature is 1.92%, humidity is 9.55%, and pH is 0.97% comparing with the conventional instruments. It is possible applying the prototype in the plant, but needs improving accuracy of humidity sensors.Keywords: Humidity, internet of things, pH, temperature, water treatment.